School allergy training promotes internal policy review and enhances staff's preparedness in managing pupils with food allergy. Issue 6 (4th August 2021) - Raptis, George; Totterdell, Rebecca; Gerasimidis, Konstantinos; Michaelis, Louise Jane; Perez‐Botella, Mercedes
Abstract: Background: Recently non‐statutory allergy management guidance for schools has been produced in the United Kingdom; however, there has been limited progress in implementing this. The aim of this study was to evaluate the effect of face‐to‐face training on self‐reported school staff preparedness in managing the severely allergic child and whether it would stimulate schools' allergy policy review. Methods: A preparedness survey was conducted prior and 2 months post‐intervention to assess the effect of training on self‐reported preparedness and perceived confidence to manage children with food allergies. Results: A sample of 18 primary schools that consented to participate were selected. Of the trained schools, 89% of the head teachers felt confident in dealing with an allergy emergency compared to 39% prior training ( p  = 0.016). Post‐intervention all but one had arranged/were considering introducing allergy awareness sessions to help pupils manage their allergies (45% pre‐training vs. post‐training 93%, p  = 0.003). Preventative measures for accidental exposure to food allergens (i.e., no food sharing policy) were adopted by all (pre‐training 61% vs. post‐training 100%, p  = 0.03). Conclusion: A face‐to‐face school allergy training programme enhances self‐reported staff preparedness and promotes internal allergy policy review in managing the needs of these children, hence addressing the current gap between recommendations and practice in schools.